Radar Sounding Confirms a Hydrologically Active Deep-Water Subglacial Lake in East Antarctica - Li, Yan; Lu, Yang; Siegert, Martin J. (Frontiers in Earth Science, 2020)
Lake CookE2, upstream of Cook Glacier in East Antarctica, is an “active” subglacial lake that experiences episodic discharge and recharge of basal water. Although around 130 active lakes are known to exist, the majority are not able to be identified by ice-sounding radar techniques, suggesting they are ephemeral and/or distributed stores of small amounts of water rather than permanent significant singular features. However, airborne radar data from Lake CookE2 reveal a bright and flat ice-bed interface, providing clear evidence of deep (>10 m) water surrounded by elevated topography. The data show the lake area is ∼46 km2; three times less than a previous estimate (145 km2) from Ice, Cloud and land Elevation Satellite (ICESat) satellite altimetry, suggesting a bias in identifying subglacial lake area from surface depressions. Using time-series altimetry from ICESat, Cryosat-2, and the Reference Elevation Model of Antarctica, we re-estimate the lake discharged ∼2.73 km3 of water (or ∼59.6 m in lake level) between February 2006 and October 2008. Subsequently, the ice surface over the lake rose steadily and experienced a mean uplift of ∼9 m between January 2011 and November 2016, indicating continuous recharge with total volume increase of ∼0.42 km3. The lake is recharging at a rate of ∼1.1 m/year, which means it could take another ∼39 years to reach the lake level that triggered the previous discharge.